(untitled) (Research, Society and Development, 2021)
Bovine Parasite Sadness (BPS) is a complex of diseases caused by non-contagious parasitic infections, being in Brazil, the main etiological agents of this disease Anaplasma marginale, Babesia bovis and B. bigemina, common in tropical and subtropical regions, generating economic losses in the development of livestock in the country, in Brazil it occurs in an endemic character. Transmission biologically is carried out by the tick Rhipicephalus (Boophilus) microplus and mechanically, in anaplasmosis, by hematophagous insects (Stomoxys calcitrans, tabanids and Haematobia irritans), contaminated fomites and in a transplacental form. The economic losses are related to the reduction in production, whether of milk or meat, temporary infertility of males and females, cost of treatment, expenses with preventive measures, care in the introduction of animals from free areas in endemic areas, leather quality and mainly, due to morbidity and mortality. The agents of both diseases are mandatory intra-erythrocyte parasites, presenting similar clinical signs, and it is possible for more than one agent to affect the same animal simultaneously, making the diagnosis of differentiation in the field difficult. Prevention is necessary, thus strengthening the immune system through inoculations of infectious agents promotes a natural defense against the disease. BPS morbidity and mortality in countries with tropical and subtropical climate is high, which is why the interest in studying it.